Pengaruh Tahfidz Al-Qur'an Terhadap Daya Ingat Anak Di TK Islam Mardisiwi Pajang Laweyan Surakarta Tahun Ajaran 2014/2015 - Nastiti, Nada Angger; , Drs. Ilham Sunaryo, M.Pd AUD; , Sri Slamet, S.Pd, M.Hum, M.Pd (2015)
The Aim of this Reasearch was to detect the effect of Tahfizul Qur'an toward Kids memorizing Skills. This was experimental Reseach. The methode of this research was 'pre-experimental design' (non design) with One Grup of Pretest-Posttest Design as the design of this research. The research subject was the students of Grup B TK Islam Mardsiwi Pajang Laweyan Surakarta Academic Year 2014/2015. This Research was held on January to May with 9 times of learning process (in class). The datas of research were collected by observation, test and documentation. The researcher applied T-Test with SPSS Program (Statistical package for The Social Sciencs) 16.0 for window as analysis technique used to test the hypothesis. Based on result of research, it could be concluded that it was true if Tahfizul Qur'an influented kids memorizing skills in TK Islam Mardisiwi Academic Year 2014/2015. It could be seen from the observation result. It was shown that the average of post-test scored was 24,30 (mean= 24,30, SD= 4,692). The average of pre-test score was 20,40 (mean= 20,40, SD= 4,858). It inreased 3,9 point on its average. From T-Test analysis scored was -9,000 (7th Attachment). It was shown that , it mean that Ho Rejected. So, it,s true if Tahfizul Qur'an influented kids memorizing skills in TK Islam Mardisiwi Academic Year 2014/2015